Distribution Characteristics of High-Background Elements and Assessment of Ecological Element Activity in Typical Profiles of Ultramafic Rock Area - Jingtao Shi; Junjian Liu; Suduan Hu; Jiangyulong Wang (Toxics)
This study investigates the weathering crust composite of serpentine, pyroxenite and granite in the Niangniangmiao area, the weathering crusts inside and outside the mining area were compared respectively, systematically revealing the distribution patterns, migration pathways, and ecological element activity characteristics of high-background elements (e.g., chromium (Cr) and nickel (Ni)) through precise sampling, the Tessier five-step sequential extraction method, and a migration coefficient model. Key findings include: (1) Element distribution and controlling mechanisms: The average Cr and Ni contents in the serpentinite profile are significantly higher than those in pyroxenite. However, the semi-weathered pyroxenite layer exhibits an inverted Cr enrichment ratio in relation to serpentinite, 1.8× and 1.2×, respectively, indicating that mineral metasomatic sequences driven by hydrothermal alteration dominate element differentiation; the phenomenon of inverted enrichment of high-background elements occurs in the weathering crust profiles of the two basic rocks. (2) Dual impacts of mining activities on heavy metal enrichment: Direct mining increases topsoil Cr content in serpentinite by 40% by disrupting parent material homology, while indirect activities introduce exogenous Zn and Cd (Spearman correlation coefficients with Cr/Ni are from ρ = 0.58 to ρ = 0.72). Consequently, the bioavailable fraction ratio value of Ni outside the mining area (21.14%) is significantly higher than that within the area (14.30%). (3) Element speciation and ecological element activity: Over 98% of Cr in serpentine exists in residual fractions, whereas the Fe-Mn oxide-bound fraction (F3) of Cr in extra-mining pyroxenite increases to 5.15%. The element activity in ecological systems ranking of Ni in soil active fractions (F1 + F2 = 15%) follows the order: granite > pyroxenite > serpentine. Based on these insights, a scientific foundation for targeted remediation in high-background areas (e.g., prioritizing the treatment of semi-weathered pyroxenite layers) can be provided.